2018
DOI: 10.1002/adhm.201800053
|View full text |Cite
|
Sign up to set email alerts
|

NanoTRAIL‐Oncology: A Strategic Approach in Cancer Research and Therapy

Abstract: TRAIL is a member of the tumor necrosis factor superfamily that can largely trigger apoptosis in a wide variety of cancer cells, but not in normal cells. However, insufficient exposure to cancer tissues or cells and drug resistance has severely impeded the clinical application of TRAIL. Recently, nanobiotechnology has brought about a revolution in advanced drug delivery for enhanced anticancer therapy using TRAIL. With the help of materials science, immunology, genetic engineering, and protein engineering, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 184 publications
0
9
0
Order By: Relevance
“…Therefore, to investigate the antitumor effect of the pro‐erufosine compounds as both gene delivery reagents and prodrugs of antiproliferative erufosine, a plasmid DNA encoding the tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL, also called Apo2L or TNFSF10) was selected. As a member of the tumor necrosis factor (TNF) superfamily, TRAIL can induce apoptosis in malignant tumors while sparing normal cells . In humans, TRAIL activates extrinsic apoptotic pathway after binding TRAIL death receptors (DRs), TRAIL‐R1 (DR4, TNFRSF10A) and TRAIL‐R2 (DR5, TNFRSF10B), and TRAIL decoy receptors that do not possess a functional death domain, TRAIL‐R3 (DcR1, TNFRSF10C) and TRAIL‐R4 (DcR2, TNFRSF10D).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to investigate the antitumor effect of the pro‐erufosine compounds as both gene delivery reagents and prodrugs of antiproliferative erufosine, a plasmid DNA encoding the tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL, also called Apo2L or TNFSF10) was selected. As a member of the tumor necrosis factor (TNF) superfamily, TRAIL can induce apoptosis in malignant tumors while sparing normal cells . In humans, TRAIL activates extrinsic apoptotic pathway after binding TRAIL death receptors (DRs), TRAIL‐R1 (DR4, TNFRSF10A) and TRAIL‐R2 (DR5, TNFRSF10B), and TRAIL decoy receptors that do not possess a functional death domain, TRAIL‐R3 (DcR1, TNFRSF10C) and TRAIL‐R4 (DcR2, TNFRSF10D).…”
Section: Resultsmentioning
confidence: 99%
“…Another study also used TRAIL to enhance the targeted antitumor activity of nanocarriers by conjugating TRAIL onto their surfaces. 26 Our biodistribution analysis showed that zA4 showed improved tumor targeting and reduced liver enrichment in a THP-1 subcutaneous tumor-bearing model (Fig. 4a, b).…”
Section: Discussionmentioning
confidence: 77%
“…administration of Ad5-based vectors is hampered by the complex interactions between virus and host proteins, leading to hepatic tropism and immune clearance, and causing the Ad5 vector to be diverted away from the desired tumor targets. [25][26][27][28] As death receptors are expressed at higher levels on the surfaces of tumor cells than on normal cells, TRAIL has been used to target tumor cells. Pan et al 28 showed that TRAIL can be conjugated with a toxic small molecule for targeted delivery of the desired chemical to tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the potential of APL prodrugs in combined antitumor therapy, we performed gene delivery experiments with pUNO1-hTRAIL. This plasmid DNA encodes the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), a member of the tumor necrosis factor (TNF) superfamily (Shi et al, 2018 ). TRAIL suppresses tumor growth by a direct and specific mechanism without affecting normal tissues (Walczak et al, 1999 ; Nair et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%